Investment Model Design Based on Financial Behavior to Achieve Financial Independence in Gen-Z - Rahmat Suryadana; Halpiah Halpiah; Hery Astika Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The financial crisis is prone to affect Gen-Z due to a consumptive lifestyle, which is both a problem and the background for conducting this research with the aim of designing financial behavior models and investment choice models that can be used to achieve the level of financial independence in the future. The study uses qualitative methodology with a design thinking approach; data collection was conducted through interviews, analyzed using triangulation techniques, with data being reduced, presented, and conclusions drawn. The validity was tested using member checking with eight informants who are working students, aged 20-25 years, with income ranging from Rp.1,000,000 to Rp.3,000,000 per month. The research findings indicate that 7 out of 8 informants tend to be consumptive, are cautious in making investment decisions, but have a target of achieving financial independence in the future. The results of this study are expected to provide a contribution as a basis for decision-making regarding changes in financial behavior patterns from consumptive to productive by allocating funds wisely to investment options that increase assets, in order to achieve the targeted financial independence in the future.